Cambridge Practice Tests for IELTS 1 - Vanessa Jakeman (Cambridge Univ. Press, 1996)
Cambridge Practice Tests for IELTS 1 is written by experienced IELTS examiners, one based in Britain and one based in Australia. The Student's Book contains an introduction to the different modules of the exam together with an explanation of the different IELTS question types and how to approach them. The inclusion of annotated keys and tapescripts for each test makes the book ideal for students working partly or entirely on their own. The Audio CDs contain listening material carefully chosen to reflect the reality of the exam in terms of timing, format and the types of speaker and accent used